Improving essay writing using the Semantic Mapping technique - Eli Nofriati (Universitas Syiah Kuala, 2017)
This research inquires whether the semantic mapping technique be used to improve the students’ ability in learning essay writing. It was designed in classroom action research which was conducted in two cycles by following the procedure of action research consisting of four steps; planning, implementing, observing and reflecting. Each cycle was carried out in three meeting. The subject of the research was the 4th semester students in unit A of the English Department, Almuslim University. The instruments used were test, observation checklist and questionnaire. The obtained data were presented and analyzed qualitatively and quantitatively. The results showed that the implementation of semantic mapping technique could improve the students’ ability in learning essay writing. This is proven by the first result found from the test given to the students. The students’ average score of the test in cycle 1 was 60 and it increased to 75 in cycle 2. The second result was obtained from the observation of the researcher’s performance and students’ activities. The percentage of the researcher’s performance in the first cycle was 75% in the level good. While, in the second cycle it increased to 88% in level very good. Next, the percentages of the students’ activities was 57% or enough in the first cycle and it increased to 79% in the level good in the second cycle. The other finding from the questionnaire was the strongly positive response (4.62) from the students to the use of the semantic mapping technique for learning essay writing.